The Moderating Role BOPO of CAR, NPL, NIM and LDR on Banking Stock Returns on the Indonesian Stock Exchange - Siagian, Sri Haryati; Sihotang, Ronny Buha; Rinendy, Jhon (IJBLE Scientific Publications Community Inc., 2024)
This research aims to determine and prove the partial and simultaneous influence of Capital Adequency Ratio (CAR), Non Performing Loans (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Operating Costs Operating Income (BOPO) on Stock returns. The second objective is to prove whether BOPO moderates the relationship between Capital Adequency Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Operating Costs and Operating Income (BOPO) on stock returns. This research uses an associative quantitative approach model, namely research to test the influence of the independent variable on the dependent variable. The population used in this research was 43 banks that were included and registered on the IDX for the 2018-2022 period. The sampling technique used uses the Purposive Sampling technique, namely that samples are taken based on certain criteria so that 20 banks are obtained with an observation period of 5 years so that 100 observation data are obtained. The data analysis technique uses Moderating regression where data analysis will use residual testing. Hypothesis testing uses the t test, F test and residual test. The results of this research prove that CAR, NIM, LDR partially have no effect on stock returns. The NPL and BOPO variables partially influence stock returns. Based on the simultaneous test, it can be concluded that the variables CAR, NPL, NIM, LDR and BOPO simultaneously have a significant effect on stock returns. The residual test results show that BOPO does not moderate the relationship between CAR, LDR, NIM and NPL on the Return variable.